Ab initio study and NBO analysis of the unimolecular decomposition kinetics of 2, 2-dimethyloxetane. (7th July 2012) - Shiroudi, Abolfazl; Zahedi, Ehsan
Theoretical study of the thermal decomposition kinetics of 2, 2-dimethyloxetane has been carried out at the B3LYP = 6-311 þ G**, B3PW91 = 6-311 þ G**, and MPW1PW91 = 6-311 þ G** levels. The MPW1PW91 = 6-311 þ G** method was found to give a reasonably good agreement with the experimental kinetics and thermodynamic parameters. Two parallel unimolecular reactions occur to give either isobutene and formaldehyde [reaction (1)] or ethene and acetone [reaction (2)]. The calculated data demonstrate that the polarization of the O1—C2 bond in reaction (1) and C4—O1 bond in reaction (2), are rate determining. The analysis of bond order and NBO charges, bond indices, synchronicity parameters, and IRC calculations suggest reactions (1) and (2) occur through a concerted and asynchronous four-membered cyclic transition state type of mechanism.